A 50 year review of basic and applied research in compound parabolic concentrating solar thermal collector for domestic and industrial applications. (15th July 2019) - Pranesh, V.; Velraj, R.; Christopher, S.; Kumaresan, V.
Graphical abstract: Abstract: In the recent years, compound parabolic concentrating (CPC) collector draws the attention of researchers and industrial developers towards meeting the downstream requirement of about 60–240 °C because of its unique features of capturing the solar rays including diffuse rays, no tracking mechanism at low to moderate concentrations, minimal heat loss and higher collector efficiency. The objective of this review is to identify the research drift towards CPC collectors for domestic and industrial applications. In this study, a comprehensive review for the CPC solar collector was carried out for the past 50 years in terms of types, historical growth in milestones, concept, design strategies, heat transfer fluids, experimental studies, theoretical studies (Numerical studies and simulation studies), applications, standards, certifications, market players and recent developments. The review, exhibited that the CPC solar collector has been continuously developed, modified and improved to achieve better collector efficiency and there is a greater potential to increase its utilization in various applications in the near future.